(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: The aim of this study is to evaluate the adoption of advance endodontic technology by general dental practitioner of Gujarat state. Methods: Around 2200 Invitation was sent to registered dental practitioners of Gujarat state by dental council of India with introductory letter and an informed consent clearly stating the purpose of the study. A questionnaire survey comprising 27 questions. The topics of the questions included endodontic continuing education (CE), professional activity, root canal preparation and instrumentation, choice of irrigants and intracanal medications, choice of obturation procedures, and utilisation of contemporary technologies. Results: 789 respondents (36%) returned completed surveys. 99% of general practitioners perform root canals; rubber dams are typically utilised by 4%, sporadically by 51%, and never by 44%. Digital radiography was employed by GPs (72%), as well as magnification (21%), and electronic apex locators (13%).